Heroines, victims and survivors: female minors as active agents in films about African colonial and postcolonial conflicts - Mdege, Norita (Centre for Film and Media Studies, 2018)
This thesis analyses the representations of girls as active agents in fictional films about African colonial and postcolonial conflicts. Representations of these girls are located within local and global contexts, and viewed through an intersectional lens that sees girls as trebly marginalised as "female," "child soldiers" and "African." A cultural approach that combines textual and contextual analyses is used to draw links between the case study films and the societies within which they are produced and consumed. The thesis notes the shift that occurs between the representations of girls in anti-colonial struggles and postcolonial wars as a demonstration of ideological underpinnings that link these representations to their socio-political contexts. For films about African anti-colonial conflicts, the author looks at Sarafina! (Darrell Roodt, 1992) and Flame (Ingrid Sinclair, 1996). Representations in the optimistic Sarafina! are used to mark a trajectory that leads to the representations in Flame, which is characterised by postcolonial disillusionment. On the other hand, Heart of Fire/Feuerherz (Luigi Falorni, 2008) and War Witch/Rebelle (Kim Nguyen, 2012), which are produced within the context of postcolonial wars, demonstrate the influences of global politics on the representations of the African girl and the wars she is caught up in. The thesis finds that films about anti-colonial wars are largely presented from an African perspective, although that perspective is at times male and more symbolic than an exploration of girls' multiple voices and subject positions. In these films, girls who participate in the conflicts are often represented as brave and heroic, a powerful indication of the moral strength of the African nationalists' cause. On the contrary, films about African postcolonial wars largely represent girls as innocent and sometimes helpless victims of these "unjust wars." The representations in the four case study films are significant in bringing to the fore some of the experiences of girls in African political conflicts. However, they also indicate that sometimes representations of girls become signifiers of ideas relating to local and global socio-political, economic, and other interests rather than a means for expressing the voices of the girls that these films purport to represent.